COMMENTARY: LEARNER-BASED LISTENING AND TECHNOLOGICAL AUTHENTICITY - Richard Robin (Language Learning and Technology, 2007)
You dropped a hundred and fifty grand on an education you could’ve picked up for a dollar fifty in late charges at the public library. Good Will Hunting, 1997Language teachers know that even the best technology cannot provide the high degree of interaction required to acquire meaningful proficiency in a foreign language. Even the most polished packages available today (and likely to be available for several years to come) cannot evaluate learner input and provide subtle shades of context-based feedback, except in the narrowest of circumstances. Technology’s dull blade is even more apparent the moment interactive orality is required. A simple phone call to a voice-automated service center reminds us to what extent mass-market speech recognition is crude and speaker-finicky, even in English. The speakers of less common languages may have to wait years before work begins on speech recognition for speakers of their languages.Off-the-shelf technology is not ready for interactive oral-aural instruction, but it has reached a level of sophistication that makes it ideal for use by the strategically independent learner to acquire and improve receptive skills in an authentic environment, if we update our definition of authenticity to include the technologically-enabled possibilities supporting a text or script1: the availability of combined texts and scripts, user-control over script delivery both in terms of speed and chunking, user-created glossing aides, captioning, etc. This technological overlay, available not just to language learners but to all users, is "authenticizing" practices that were once considered inauthentic. No longer are such devices part of the specialized landscape of the L2 learner; instead they make up the everyday L1 machine-mediated world of listening. That has implications for the demands learners make of themselves and the tasks that they choose. It also leads us to reexamine the value of pre-packaged listening comprehension materials in which L2 listeners are guided in listening strategies but are not encouraged to make use of technological innovations that native listeners are coming to use on a regular basis.A brief survey of the available user-directed modifications to online scripts leads one to the idea that in the immediate future — the next five to ten years — the frontier in language learning and technology will not be found in what program does what better, but rather which students use off-the-shelf technology to best facilitate their own learning in their own learning style. Just as we began to teach metacognitive acquisition strategies, such as the use of background knowledge and prediction in the 1980s (see Nunan, 1999; Omaggio-Hadley, 2001; and Ur, 1984) for summaries of research and practice then and now), we should now teach meta-technical skills to language learners, rather than setting them out on a closed loop. Others have come to the same conclusion that technological literacy is an essential component of the language acquisition strategic toolbox (Godwin-Jones, 2000; Hubbard, 2004; LeLoup & Ponterio, 2000; Richards, 2000;). Effective users of raw electronic resources, such as easily repeatable video clips, captions, and even translation bots will bring a wider variety of input at the proper level for a broader range of learning styles than could possibly be made available in any pre-packaged closed-track program.In listening comprehension, attention over the last twenty-five years has turned from adapted scripts to authentic audio and video in which we scaffold "real media" with remediated tasks (pre- and post-script activities) instead of changing the media itself. Yet despite the scaffolding, authentic materials, particularly where they involve a non-interactive flow of speech such as radio, TV, and movies, remain a challenge, especially in the beginning stages of language learning. The audio is too fast. Or acoustically difficult. Or too heavily culturally referenced. Or has too much slang. Take the scaffolding away, and the learner’s activity falls apart.As a result, materials designers continued to concentrate on wrapping the materials in better wrappers, e.g., by adjusting the task and occasionally modifying the script (we call it semi-authentic) rather than teaching learners to use the technology to mediate the script. Such sites abound on the web. Many, such as SCOLA, rely on authentic video and audio with wraparound exercises and transcripts. Others such as Randall's ESL Cyber Listening Lab or the NCLRC’s Simplified Russian Radio Site (created by the author of this article) resort to semi-authentic audio.On the other hand, commonly available technological fixes can be called upon for greater degrees of remediation. At one time, such modifications were considered distinct from "authentic" (Chapelle, 1998), but today they all part of the world of the native listener that involves neither scaffolding nor semi-authenticity. Here are some of the more prominent devices.